2020
DOI: 10.3168/jds.2019-17264
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transglutaminase alters the immunogenic potential and cross-reactivity of horse and cow milk proteins

Abstract: Horse milk is a valuable raw material and a very attractive alternative for scientific research to address the issue of cow milk (CM) allergy due to its protein profile. A decrease in immunoreactive properties can be achieved by thermal, enzymatic, and hydrolytic processing. Therefore, the aim of this study was to explore the possibility of reducing the immunoreactivity of horse milk proteins by microbial transglutaminase (TG) polymerization. To determine how TG linking alters immunoreactivity under simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
1
7
0
1
Order By: Relevance
“…This is consistent with the data obtained when specific inhibition ELISA was performed on CN and WP samples ( Figure 2 c,d). Different results were found by Fotschki et al, who showed that polymerization with TG decreased β-LG immunoreactivity and increased IgE binding of α-CN [ 20 ]. However, they used polyclonal rabbit antibodies, obtained from rabbits immunized against commercial purified allergens instead of human sera from naturally sensitized allergic patients.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…This is consistent with the data obtained when specific inhibition ELISA was performed on CN and WP samples ( Figure 2 c,d). Different results were found by Fotschki et al, who showed that polymerization with TG decreased β-LG immunoreactivity and increased IgE binding of α-CN [ 20 ]. However, they used polyclonal rabbit antibodies, obtained from rabbits immunized against commercial purified allergens instead of human sera from naturally sensitized allergic patients.…”
Section: Resultsmentioning
confidence: 82%
“…WP, due to their compact globular structures, cross-linked less efficiently [ 17 ]. Although there is no specific legislation about minimum or maximum quantities of TG allowed to be added to food products in the European Union or in the United States, most studies that addressed the use of TG in dairy foods use a maximum of 100 U/g of protein [ 19 , 20 ]. We evaluated the use of 1000 U/g of protein to assess whether higher enzyme activity could result in higher crosslinking efficiency, but although polymerization increased slightly compared to 100 U/g, it was not enough to convert all monomeric proteins into polymers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antigenic epitope of amandin was destroyed or buried, and its potential allergenicity was reduced. Structural and conformational changes caused by processes such as food processing alter the immunoreactivity of proteins ( Fotschki et al, 2020 ). The reduced potential allergenicity of amandin might be mainly due to the absence of disulfide bonds, decreased solubility such as formation of protein–polyphenol insoluble conjugates, and burial of antigenic epitopes ( Chhabra et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Трансглутаминазу иногда называют «природным клеем», так как она участвует в процессах: свёртываемости крови, синтезе кожи, модификации клеточного матрикса и других процессах. В 1989 году японскими учеными была получена трансглутаминаза из штамма почвенных бактерий Streptoverticillium mobaraense, которые в больших количествах синтезируют легко очищаемую ТГ [11,12,13,14].…”
Section: Introductionunclassified